2020
DOI: 10.3390/ijms21082812
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Affects Mitotic Segregation of Human Chromosomes Bound to Stress-Induced Satellite III RNAs

Abstract: Heat shock activates the transcription of arrays of Satellite III (SatIII) DNA repeats in the pericentromeric heterochromatic domains of specific human chromosomes, the longest of which is on chromosome 9. Long non-coding SatIII RNAs remain associated with transcription sites where they form nuclear stress bodies or nSBs. The biology of SatIII RNAs is still poorly understood. Here, we show that SatIII RNAs and nSBs are detectable up to four days after thermal stress and are linked to defects in chromosome beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
(107 reference statements)
0
16
0
Order By: Relevance
“…Several studies have emphasized on the transcriptional and epigenetic status of the pericentromeric satellite transcripts that if altered enhances the risk of malignancies (Giordano et al, 2020; Zhu et al, 2018). Since we observed that the level of SatIII expression varies between unstressed and heat‐shocked human colon and breast cancer cells, we further decided to investigate whether SatIII transcripts are required for cancer cell progression.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have emphasized on the transcriptional and epigenetic status of the pericentromeric satellite transcripts that if altered enhances the risk of malignancies (Giordano et al, 2020; Zhu et al, 2018). Since we observed that the level of SatIII expression varies between unstressed and heat‐shocked human colon and breast cancer cells, we further decided to investigate whether SatIII transcripts are required for cancer cell progression.…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of polymorphisms affecting the HSEs present on 9q12 or Yq12 themselves is unlikely given the large number of repetitive motifs, thus limiting the impact of a few mutational events at the Yq12 locus. Intriguingly, on the basis of a recent article showing that cis accumulation of SATIII transcripts causes the mis-segregation of the chromosome from which they originate (Giordano et al 2020 ), the expression of SATIII RNAs and formation of primary nSBs on chromosome Y may represent a significant source of instability for this chromosome too. However, while we were able to confirm the large percentage of chromosome lagging affecting chromosome 9 on HeLa cells used as a control, we were not able to detect chromosome instability in H1080 cell line submitted to heat shock followed or not to different time of recovery at 37 °C (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have emphasized on the transcriptional and epigenetic status of the pericentromeric satellite transcripts that if altered enhances the risk of malignancies Giordano et al, 2020). Since, we observed that the level of SatIII expression varies between unstressed and heat shocked-human colon and breast cancer cells, we further decided to investigate whether SatIII transcripts are required for cancer cell progression.…”
Section: Satiii Transcription Promotes Proliferation Of Hct-15 (Colon) and Zr-75-1 (Breast Cancer) Cellsmentioning
confidence: 99%